A critical role of lipid rafts in the organization of a key FcγRIIa-mediated signaling pathway in human platelets - Bodin, Stéphane; Viala, Cécile; Ragab, Ashraf; Payrastre, Bernard (Thrombosis and Haemostasis, 2003)
The involvement of platelet FcγRIIa in heparin-associated thrombocytopenia (HIT) is now well established. However, the precise sequence of molecular events initiated by FcγRIIa cross-linking in platelets remains partly characterized. We investigated here the role of lipid rafts in the spatio-temporal organization of the FcγRIIa-dependent signaling events. Upon cross-linking, FcγRIIa relocated in rafts where the kinase Lyn and the adapter LAT were among the major phosphotyrosyl proteins. Upon stimulation by HIT sera, the second messenger phosphatidylinositol 3,4,5-trisphosphate (PtdIns(3,4,5)P3) accumulated in rafts in a P2Y12 adenosine diphosphate (ADP) recep- tor-dependent manner. PtdIns(3,4,5)P3 was then essential to specifically recruit phospholipase Cγ2 (PLCγ2) to these membrane microdomains. Controlled disruption of rafts by methyl γ-cyclodextrin reversibly abolished PtdIns(3,4,5)P3 production, PLC activation and platelet responses induced by FcγRIIa cross-linking without affecting the tyrosine phosphorylation events. This work demonstrates that platelet rafts are essential for the integration of a key signaling complex leading to the rapid production of PtdIns(3,4,5)P3 and in turn PLCγ2 activation during HIT.
Keywords: FcγRIIa; platelets; rafts; phosphoinositides; P2Y12